Sudden Death Due to Mechanical Failure of Prosthetic Aortic Valve: A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
One of the major reasons of sudden natural deaths is cardiac arrests. Forensic pathologists rarely encounter sudden deaths in individuals who are already suffering from a cardiac problem. In case the deceased has undergone surgery for such a pre-condition then the treating physician usually issues a cause of death certificate. Failure of cardiac valve prosthesis can lead to sudden death. A 45-year-old male suddenly died 3 ½ months after he underwent aortic valve replacement with size 21 TTK CHITRA TILTING DISC VALVE under cardio pulmonary bypass for rheumatic aortic stenosis and regurgitation. The autopsy revealed that death occurred due to a mechanical failure of the prosthetic aortic valve – after ruling out all other possible causes.
Keywords: Sudden death; Rheumatic heart disease; Aortic stenosis; Aortic regurgitation; Prosthetic valve